Qiyam Bi Al-‘Adl dalam Pendidikan Perspektif Hadis - Fatiya Nazhifa; Hafsyah Dwi Khoiriyah Saragih; Marianum Marianum; Dwi Meutia Hasni (Jurnal Budi Pekerti Agama Islam, 2026)
Justice is a fundamental value in Islamic teachings. The Qur’an emphasizes the importance of upholding justice objectively and consistently, without regard to differences in ethnicity, race, or skin color. As educators, teachers bear a significant responsibility to act as objective and impartial role models in the classroom. However, challenges in the field of education frequently manifest in the form of discriminatory actions, whether intentional or unintentional, resulting from situational and emotional factors. This study employs a qualitative approach using library research and data collection techniques that draw upon hadith texts from primary sources, relevant educational literature, and verses from the Qur’an. The findings indicate that educators’ implementation of fair attitudes can enhance students’ self-confidence and foster a harmonious and tolerant learning environment. Conversely, discriminatory behavior whether intentional or unintentional that directly contradicts the humanitarian principles taught in Islam can have significant negative psychological impacts, ranging from a loss of motivation to learn and self-confidence to the risk of dropping out of school and the development of an intolerant character. Just as the Prophet demonstrated how to instill a sense of fairness in students through setting a good example and fostering good habits and his practice of treating men and women equally in their right to education.